Strategi Pemanfaatan Instagram Oleh PT Tip Top Sebagai Media Komunikasi Pemasaran Digital - Farhan Dzikri; Dholley Dwi Jatmiko Latabulo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Tip Top is a company engaged in sharia-based supermarkets. Tip Top utilizes Instagram social media as a marketing communication medium; therefore, it takes the right strategy and is able to maximize marketing activities through digital. Reviewing the marketing communication elements, the purpose of this study is to find out how the Tip Top strategy utilizes Instagram social media as a marketing communication medium, using a post-positivism paradigm and a qualitative approach. The results of this study are strategies for utilizing Instagram's social media using Instagram feed features, Instagram stories, Instagram live and Instagram ads to support marketing activities. In addition, digital marketing activities aim to strengthen the identity of the Tip Top brand that breathes Islam and increases brand awareness from the public